Security and vulnerability analysis of web applications - Le, Ha Thanh (2011)
Vulnerabilities in Web applications have grown exponentially over the last decade. For effective remediation, more comprehensive analytical models are necessary. This work introduces a property-based description model for Web-based vulnerability analysis. We present the theoretical basis of this property-based analysis model. The analysis of cause and consequence views of the model can support inference of the cause of vulnerability as well as the evaluation of vulnerability impact and severity. The effectiveness of the model is then demonstrated by its applications on real world vulnerabilities.